IMPROVING THE STUDENTS’ ABILITY IN MASTERING READING COMPREHENSION THROUGH THREE-TWO-ONE (3-2-1) STRATEGY - Misnawati, Misnawati; Novita, Novita (Jurnal Pendidikan Almuslim, 2019)
This thesis entitled “Improving the Students’ Ability in Mastering Reading Comprehension through Three-Two-One (3-2-1) Strategy (A Collaborative Classroom Action Research to the First Year Students of MAN Gandapura)”. From the title above, the researcher put two problems of this research with the questions; first, how is the Three-Two-One (3-2-1) strategy improve the students’ ability in mastering reading comprehension? Second, how does the students’ respond toward the implementation of Three-Two-One (3-2-1) strategy in teaching reading comprehension?. The purposes of the research were; To find out Three-Two-One (3-2-1) strategy improve the students’ ability in mastering reading comprehension and to know the students’ respond toward the implementation of Three-Two-One (3-2-1) strategy in teaching reading comprehension. To answer the research questions, the researcher used collaborative classroom action research as methodology of the research. Therefore, the researcher did collaboration with English teacher to do the research. This research was conducted at MAN Gandapura. The subject of the research consisted of twenty nine students. This research was qualitative research. The researcher used test, observation sheet, questionnaires, and field notes as the instrument of the research. The researcher and teacher got the mean score of students’ test in the cycle I was 55.03, and test in the cycle II was 71.16. Therefore, the researcher concluded that Three-Two-One (3-2-1) strategy had improve students’ ability in reading comprehension, this strategy can solve the students’ problems in learning reading comprehension in the classroom, and also this strategy brings the new situations for the students to be active in reading comprehension in the classroom. Key words: Reading Comprehension, Three-Two-One (3-2-1) Strategy.